2021
DOI: 10.1002/hep4.1853
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 Infections Among Patients With Liver Disease and Liver Transplantation Who Received COVID‐19 Vaccination

Abstract: Many safe and effective severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) vaccinations dramatically reduce risks of coronavirus disease 2019 (COVID‐19) complications and deaths. We aimed to describe cases of SARS‐CoV‐2 infection among patients with chronic liver disease (CLD) and liver transplant (LT) recipients with at least one prior COVID‐19 vaccine dose. The SECURE‐Liver and COVID‐Hep international reporting registries were used to identify laboratory‐confirmed COVID‐19 in CLD and LT patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 29 publications
0
38
1
6
Order By: Relevance
“…The same authors found that two doses of COVID-19 mRNA vaccine were associated with a lower incidence of COVID-19 infection, symptomatic COVID-19 and COVID-19-related death in LT recipients 140. In patients with CLD and LT recipients, vaccination against SARS-CoV-2 appears to result in favourable outcomes as attested by the absence of mechanical ventilation, ICU or death among fully vaccinated patients 141. Therefore, AASLD and EASL recommend prioritisation for vaccination of patients with CLD, including those with immune-mediated liver diseases, HCC and LT recipients 142 143.…”
Section: Vaccination Against Sars-cov-2 In Patients With Liver Diseasementioning
confidence: 95%
See 1 more Smart Citation
“…The same authors found that two doses of COVID-19 mRNA vaccine were associated with a lower incidence of COVID-19 infection, symptomatic COVID-19 and COVID-19-related death in LT recipients 140. In patients with CLD and LT recipients, vaccination against SARS-CoV-2 appears to result in favourable outcomes as attested by the absence of mechanical ventilation, ICU or death among fully vaccinated patients 141. Therefore, AASLD and EASL recommend prioritisation for vaccination of patients with CLD, including those with immune-mediated liver diseases, HCC and LT recipients 142 143.…”
Section: Vaccination Against Sars-cov-2 In Patients With Liver Diseasementioning
confidence: 95%
“…The results of these studies on immunological response appear promising when contextualised in the current pandemic setting where hybrid immunity (mediated by infection and vaccine) becomes increasingly frequent. Encouraging data are available on the attenuation of severe forms in vaccine-LT-treated patients 158. However, considering that several reports have confirmed a low humoral-mediated and T cell-mediated response in patients with CLD and LT, a revised schedule of vaccine administration was advocated in these populations 159…”
Section: Vaccination Against Sars-cov-2 In Patients With Liver Diseasementioning
confidence: 99%
“…Currently, there is a lack of literature on the management of COVID-19 patients who develop chronic cholestasis after recovery. Furthermore, it is well known that vaccinations can prevent severe COVID-19 and improve outcomes 11 , 12 . However, the effect of vaccines on COVID-19 induced cholestasis is unknown.…”
Section: Author Contributionsmentioning
confidence: 99%
“…These findings appear to be consistent with a recently published paper reporting that SARS‐CoV‐2 vaccination reduces severe disease in patients with cirrhosis and SOTRs. [ 32 ]…”
Section: Discussionmentioning
confidence: 99%